Flood-tolerant rice improves climate resilience, profitability, and household consumption in Bangladesh - CGIAR Research Program on Rice (2021)
• The main drivers of adoption are access to information on Flood-tolerant rice Sub1 through neighbors, farmer organizations, and training. • Adoption of Sub1 rice increases rice yield (6.0% higher), profit (55.0% higher), and household consumption (15.0% higher). • Non-adopters could benefit if they adoptd sub1 rice by an increase of approximately 8% in rice yield, 48% of profit and 15% of household consumption